Chronic treatment with apelin, losartan and their combination reduces myocardial infarct size and improves cardiac mechanical function. (17th December 2019) - Abbasloo, Elham; Najafipour, Hamid; Vakili, Abedin
Abstract: The renin–angiotensin system (RAS) has a deleterious and apelin/APJ system has protective effect on the ischaemic heart. The collaboration between these systems in the pathophysiology of myocardial infarction is not clear. We determined the effect of chronic pretreatment with apelin, losartan and their combination on ischaemia–reperfusion (IR) injury in the isolated perfused rat heart and on the expression of apelin‐13 receptor (APJ) and angiotensin type 1 receptor (AT1R) in the myocardium. During 5 days before the induction of IR, saline (vehicle), apelin‐13 (Apl), F13A (apelin antagonist), losartan (Los, AT1R antagonist) and the combination of Apl and Los were administered intraperitoneally in rats. Ischaemia was induced by left anterior descending (LAD) artery occlusion for 30 minutes followed by reperfusion for 55 minutes in the Langendorff isolated heart perfusion system. Pretreatment with Apl, Los and the combination of Apl + Los significantly reduced infarct size by about 30, 33 and 48 percent respectively; and significantly improved the left ventricular function indices such as left ventricular developed pressure (LVDP), left ventricular end‐diastolic pressure (LVEDP) and rate pressure product (RPP). IR increased AT1R protein level but it did not change APJ significantly. AT1R expression was reduced in groups treated with Apl, Los and Apl + Los. Findings showed that chronic pretreatment with apelin along with AT1R antagonist had more protective effects against IR injury. Combination therapy may diminish the risk of IR‐induced heart damage, by reducing AT1R expression, in the heart of patients with coronary artery disease that are at the risk of MI and reperfusion injury.